Intrastromal Corneal Ring Segments for visual rehabilitation of keratoconus patients - Marques, Manuel (2020)
Purpose Visual rehabilitation is an important part of keratoconus treatment. Glasses or contact lenses are usually sufficient in mild cases. Advanced disease may require surgical treatment. Intrastromal corneal ring segments (ICRS) implantation is an effective treatment. However, surgical planning is in constant evolution and the visual results are hard to predict. We aim to assess predictive factors of the visual results, determining the best cases for this treatment.   Material and Methods: Retrospective analysis of successful ICRS implantation in our hospital. Refractive and topographical data in pre and postoperative setting was analyzed in order to identify predictive factors for success. INTACS-SK® ring segments were used, according to the plan recommended by the manufacturer.   Results Sixty-five surgeries were analyzed. Both uncorrected visual acuity (UCVA) and best corrected visual acuity (BCVA) showed significant improvement after surgery (0.11±0.11 to 0.28±0.20 and 0.48±0.22 to 0.63±0.20, respectively). Refractive and keratometric values also improved significantly. BCVA improved in 43 eyes (67%), with gain of at least 2 Snellen lines in 28 eyes (43%). Post-op BCVA was negatively correlated with pre-op refraction, corneal thickness and corneal curvature. Visual improvement was negatively correlated with pre-op corneal astigmatism and steep K. Patients with steep K lower than 47.5D and corneal astigmatism lower than 3.75D had better results.   Conclusions ICRS implantation is effective in improving visual acuity, refraction and corneal shape. Eyes with more advanced disease (higher astigmatism and corneal curvature) have worse results, perhaps being better suited for other treatments, such as keratoplasty. It is possible that a different type of ring segment or improved surgical planning could improve the results.